2007
DOI: 10.1002/art.22632
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin reverses endothelial dysfunction and increased vascular oxidative stress in rat adjuvant‐induced arthritis

Abstract: Objective. To investigate the effect of statins on vascular dysfunction in rat adjuvant-induced arthritis (AIA).Methods. Fluvastatin (5 mg/kg/day) was administered orally to rats with AIA, for 21 days after the onset of arthritis. The vasodilatory response to acetylcholine of aortic rings isolated from rats with AIA that were not treated or were treated with fluvastatin and from normal rats was determined. The amounts of 4-hydroxy-2-nonenal (HNE) and nitrotyrosine in aortas were measured by Western blotting. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
60
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 56 publications
16
60
2
Order By: Relevance
“…In contrast, the expression of eNOS did not differ between AIA rats and controls. This result is not in accordance with the data of Haruna et al (12,13), who reported increased eNOS expression in aortas from AIA rats with endothelial dysfunction. However, in their study, neither the activity of NOS nor the functional impact of L-NAME was investigated, and it was not determined whether the eNOS overexpression was associated with increased eNOS activity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, the expression of eNOS did not differ between AIA rats and controls. This result is not in accordance with the data of Haruna et al (12,13), who reported increased eNOS expression in aortas from AIA rats with endothelial dysfunction. However, in their study, neither the activity of NOS nor the functional impact of L-NAME was investigated, and it was not determined whether the eNOS overexpression was associated with increased eNOS activity.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, we investigated endothelial function in the AIA model, which is commonly accepted as having many histologic and clinical features in common with human RA (31) and which is widely used to predict clinical efficacy of new therapies in RA (32). In accordance with previous studies (12)(13)(14)(15)(16)(33)(34)(35), our data show that endothelial function assessed by the vasodilating response to ACh is impaired in AIA rats. We also demonstrated that endothelial dysfunction correlates with disease activity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Fluorescence spectrometry of tissue O 2 -production was carried out using the fluorogenic oxidation of DHE to ethidium as a measure of O 2 -, as previously described. 16 The renal cortex of the right kidney obtained from each rat was cut into small pieces, and the glomeruli were isolated by the mechanical graded sieving technique. After isolation, the purity of the final suspension was determined by light microscopic examination.…”
Section: Glomerular Damage Scorementioning
confidence: 99%
“…We used Dahl salt-sensitive hypertensive (DS) rats to examine the NOS coupling statement in the kidney using the dihydroethidium (DHE) assay 16 and in vivo NO and ROS imaging, 17 and examined autoregulation capacity by measuring renal microvascular responses to step changes in renal perfusion pressure. Moreover, to elucidate whether angiotensin receptor blockade (ARB) has a beneficial effect against eNOS uncoupling and renal autoregulation, we examined DS rats treated with telmisartan, an angiotensin receptor blocker.…”
Section: Introductionmentioning
confidence: 99%